Multidimensional family support and pre-procedural anxiety in patients undergoing cardiac catheterization: A cross-sectional study - Suryagustina; Putria Carolina (Nursing and Health Sciences Journal (NHSJ), 2026)
Cardiac catheterization frequently induces severe pre-procedural anxiety, necessitating effective psychosocial interventions to ensure hemodynamic stability and patient cooperation. This study investigated the relationship between multidimensional family support and anxiety levels among patients scheduled for invasive cardiac procedures. A quantitative cross-sectional design was utilized, enrolling 34 patients selected through consecutive sampling at a regional tertiary hospital in Central Kalimantan, Indonesia. Researchers measured familial assistance using a validated 20-item questionnaire encompassing emotional, informational, appraisal, and instrumental dimensions. Patient anxiety severity was concurrently assessed utilizing the standardized Hamilton Anxiety Rating Scale (HARS). Spearman's rank correlation test evaluated the statistical association between these primary psychosocial and clinical variables. The majority of participants reported adequate familial backing and experienced predominantly mild to moderate psychological distress prior to the diagnostic intervention. Statistical analysis demonstrated a significant, very strong negative correlation between family support (p = -0.888) and anxiety levels (p = 0.003). Individuals receiving comprehensive assistance from their relatives consistently exhibited significantly lower preoperative apprehension compared to those lacking robust social networks. Robust social backing effectively buffers the psychological impact of invasive cardiovascular diagnostics by enhancing internal coping resources and mitigating uncertainty. Nurses should prioritize structured educational sessions to equip families with the knowledge needed to provide effective emotional support. Healthcare institutions must integrate structured family-centered protocols into routine preoperative care to optimize patient readiness and minimize perioperative emotional turmoil.